Background and Foreground: Connections and Distinctions When Health Professions Faculty Teach Both Interprofessional Collaborative Practice and Quality Improvement—A Case Study - Katherine Stevenson; Johan Thor; Marcel D’Eon; Linda A Headrick; Boel Andersson Gäre (Journal of Medical Education and Curricular Development)
OBJECTIVES Despite decades of effort, programs continue to struggle to integrate competencies related quality improvement (QI) and interprofessional collaborative practice (ICP) into health professions education. Additionally, while QI and ICP may seem intuitively linked and there exists some examples of a coordinated approach, the literature regarding competencies, including knowledge, skills, and attitudes (KSAs), is still largely focused on QI and ICP as separate fields of knowledge and practice. This study explored distinctions and connections between quality improvement (QI) and interprofessional collaborative practice (ICP) competency domains in health professions education. METHODS The authors used a qualitative case study approach with an instrumental case, that is, the University of Missouri-Columbia (MU), where QI and ICP were intentionally integrated as part of core curricula in health professional schools and programs. Eleven faculty members from medicine, nursing, pharmacy, and health care administration participated in interviews exploring their teaching choices in either classroom or clinical settings. RESULTS Study participants defined the goal of teaching QI and ICP as enabling learners to deliver safe and patient-centered care and described the knowledge and skills required for QI and the attitudes and skills required for ICP. Furthermore, they described the relationship between QI and ICP as one mediated by systems thinking, where ICP is backgrounded as a critical pre-requisite and QI is foregrounded as a vector for developing interprofessional competencies. CONCLUSIONS The MU case elucidates the potential synergies that occur when faculty address quality improvement and interprofessional collaborative practice competencies with an integrated approach that leverages connections, while also respecting distinctions. For health professions education programs looking to improve the effectiveness and efficiency of their curricular approach to these fields, it may be fruitful to consider ICP as background and QI as foreground, remembering that without each other, ICP risks losing meaning and QI risks losing impact.